Influence Use Digital Payment Qris, And Financial Literacy on Gen Z's Consumptive Behavior - Santa Oktaviana Sinaga; Tiorika Nababan; Ananda Anugrah Nasution (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of Digital Payment QRIS and Financial Literacy on the Consumptive Behavior of Generation Z at the Faculty of Psychology, Prima Indonesia University. The research employs an associative quantitative approach, collecting data through a Likert scale questionnaire distributed to 90 respondents selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS. The findings indicate that Digital Payment QRIS has a positive and significant effect on consumer behavior, suggesting that the convenience and speed of digital transactions tend to increase impulsive buying among students. Conversely, Financial Literacy has a negative and significant effect on consumptive behavior, meaning that the higher the students' financial understanding, the lower their tendency to engage in consumptive behavior. Simultaneously, both variables contribute 94.5% to the consumptive behavior of Generation Z. These results highlights the importance of practical financial educational and mindful use of digital financial services to help students manage their spending more responsibly.